2021
DOI: 10.3390/land10101027
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Divergence and Driving Mechanisms of Urban-Rural Sustainable Development: An Empirical Study Based on Provincial Panel Data in China

Abstract: China’s long-standing urban-rural dichotomy has led to a widening gap between urban and rural areas, posing a huge challenge to the sustainable development of Chinese society. This paper adopted the subjective-objective weighting method, coupled coordination degree model, and geographically weighted regression model to conduct urban-rural sustainable development research on 31 provincial administrative regions in China and discussed their spatial-temporal divergence and driving mechanisms during 2007–2018. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Therefore, it is necessary to study the problem of convergence. Recently, most studies on convergence concentrate on the gap and junction of the regional economy, and other research has shown the convergence of new urbanization growth [ 24 ]. However, the study on the regional gap and growing convergence of urban-rural integration development remains insufficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is necessary to study the problem of convergence. Recently, most studies on convergence concentrate on the gap and junction of the regional economy, and other research has shown the convergence of new urbanization growth [ 24 ]. However, the study on the regional gap and growing convergence of urban-rural integration development remains insufficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1) economic development, such as per capita gross domestic product (GDP), industrial structure, per capita fiscal expenditure [14], fixed asset investment [15], Urban-Rural Sustainable Development [16].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…They are no longer satisfied with simple ratio methods or Theil index methods, and have turned to more comprehensive methods such as the entropy method [15], analytic hierarchy process [16], and coupling models [17]. For example, Wei C. et al (2021) used the entropy method to assess the coupling coordination development of urban-rural areas, revealing spatial-temporal differentiation patterns [18]. Qiao G. et al (2023) analyzed the coupling coordination degree between rural revitalization and new urbanization, highlighting significant spatial disparities [19].…”
Section: Introductionmentioning
confidence: 99%